The Behavior of the Annual Electricity Demand and the Role of Economic Growth in Colombia - Grimaldo-Guerrero, John William; Silva-Ortega, Jorge Ivan; Candelo-Becerra, John E.; Balceiro-Alvarez, Bernardo; Cabrera-Anaya, Omar (International Journal of Energy Economics and Policy, 2021)
The electricity demand forecast allows countries to establish long-term plans and objectives for identifying gaps, selecting strategies, and designing the electric power system's architecture. Traditional models use GDP as the primary variable to forecast the electricity demand. The work presents an analysis of the relationship between electricity demand and economic growth, using regression methods with one or more variables. The GDP and sectoral GDP data was provided by Banco de la República de Colombia. The results validate the traditional model and offer alternative models that can relate the economy's different sectors with the electricity demand. Keywords: Energy Forecasting; Electricity Demand; Macroeconomics Indicator; Backward, Forward, and Stepwise methods. JEL Classifications: Q41, Q43, Q47. DOI: https://doi.org/10.32479/ijeep.11386